Targets of statins intervention in LDL-C metabolism: Gut microbiota - Sun, ChangXin; Wang, ZePing; Hu, LanQing; Zhang, XiaoNan; Chen, JiYe; Yu, ZongLiang; Liu, LongTao; Wu, Min (Frontiers in Cardiovascular Medicine, 2022)
With the deepening of research on the gut microbiota, the mechanisms by which the microbiota mediates the occurrence and development of metabolic diseases have gradually become clear. Therefore, the gut microbiota is considered a new "metabolic organ." Abnormal lipid metabolism leads to elevated blood lipids, among which low-density lipoprotein cholesterol (LDL) can lead to ectopic lipid deposition and associated metabolic diseases; hence, statins are widely used as effective LDL-lowering drugs. In recent years, the gut microbiota and statins have received increasing attention, and the pathways by which statins reduce LDL by affecting the abundance of microbiota have gradually surfaced. In this review, we discuss the processes of gut microbiota and its metabolites involved in lipid metabolism and the effect of statins on the gut microbiota. In this way, we summarize the mechanisms of gut microbiota-mediated lipid-lowering by statins, including the PPARγ-AMPK-SREBP1c/2-HMGCR, FXR and TGR5-related, and LPS-TLR4-Myd88 pathways. This may have a positive impact on understanding individual differences in statin efficacy and statin-lowering LDL strategies.